Pengaruh Perbedaan Jenis Kulit Kopi dan Penambahan Daun Rosemary (Rosmarinus officinalis) terhadap Karakteristik Cascara Celup - Awido Butar-Butar; Sunardi; Reni Astuti Widyowanti (Program Studi Teknologi Hasil Pertanian, 2024)
The objectives of this study are: (1) to determine the effect of coffee skin type with the addition of rosemary leaf powder on the characteristics of cascara dip; (2) to know the formulation of the type of coffee skin with the addition of rosemary leaf powder that produces the most preferred cascara dip for the panelists. The latest in this study is an innovation to eliminate the taste of cascara with rosemary leaf powder, as well as practical and contemporary presentation in the form of dip cascara. The research will use 2 factors. The first factor is type coffee skin (A) with 3 levels, namely A1= arabica coffee skin, A2= robusta coffee skin, and A3 = arabica and robusta coffee skin blend with a 1:1 ratio. The second factor is the addition of rosemary leaf powder by weight of cascara with 3 levels, namely B1= 2%, B2= 4%, and B3= 6%. The results of the study showed that: (1) The type of coffee skin with the addition of rosemary leaves had an effect on the tannin content, taste, and color of the cascara dip. But it has no effect on antioxidant levels, caffeine levels, total acidity, total color difference, and aroma. (2) Cascara dip made from arabica coffee bark with the addition of 2% rosemary leaves (A1B1) is a cascara that consumers prefer (somewhat like) has an antioxidant level of A1B1 37.397%, caffeine 0.97%, tannins 0.0080, total acid 0.109, total color difference 29.173, moisture content 5.57% and ash content 1.815%.